Eco-Digital Pedagogy: Current Situation and Its Solution to Enhance Pre-Service Teachers’ Pedagogical Competence - Kurniawan, Edi; Akhyar, Muhammad; Muryani, Chatarina; Asrowi, Asrowi (FKIP Universitas Lampung, 2025)
Eco-Digital Pedagogy: Current Situation and Its Solution to Enhance Pre-Service Teachers’ Pedagogical Competence. Objective: This study aims to: 1) explore the existing model implemented in the classroom related to pedagogical learning, the use of technology, and environment-based learning; and 2) propose eco-digital pedagogy to improve the competence of 21st-century pre-service (trainee) teachers. Methods: This study was qualitative with didactical research design, focusing on the analysis of the implementation of pedagogical courses at the Geography Education Study Program at Universitas Negeri Semarang (UNNES). The subjects of this research were selected using a purposive technique and consist of twelve students who had completed pedagogical courses. Primary data, collected from interviews, were then complemented with secondary data from previous research, books, and online articles related to implementing eco-pedagogy and digital pedagogy. Findings: The results indicate that pedagogical skills learning, technology utilization, and environment-based learning have been applied, but the intensity, variety of methods, and comprehension are relatively low. Lecturers often underutilize technology as an educational tool and do not fully comprehend the ecological principles underpinning sustainable development. Technology adaptation is limited to the use of LMS, while eco-related materials are minor and not practicable. This condition requires improvement, one of which is through eco-digital pedagogy, a combination based on digitalization and awareness of ecology. It can be implemented through several steps: 1) designing a suitable curriculum, 2) providing adequate facilities, 3) increasing hands-on practice with real and relevant situations, 4) enriching pedagogical learning methods, and 5) utilizing platforms or digital media as a teaching space and a campaign for promoting environmental awareness. Conclusion: Digital and eco-related learnings are found to be minimally implemented, thus the learning outputs are not optimal. Eco-digital pedagogy can be applied to enhance the learning quality of pedagogical courses. Keywords: eco-digital pedagogy, geography trainee teacher, 21st century.